62. Syntaxonomic and nomenclatural novelties in the wetland vegetation of Baikal Siberia (Russian Federation) - Chepinoga, Victor (Lazaroa, 2014)
This paper presents some results of research into vegetation diversity in water bodies and streams in Baikal Siberia, aregion in southeast Siberia. The article contains the original diagnoses of five new associations (Callitricho palustris-Subularietumaquaticae, Lemno turioniferae-Thacletum natantis, Ceratophyllo demersi-Eleocharitetum mamillatae, Cariceumpseudocuraicae, Scirpetum orientalis), the typification of one existing association name (Glycerietum spiculosae),and the correction of another name: Tephroseridetum palustris Mirkin & al. 1985.